Assessment of Runoff and Drainage Conditions in a North Banat Sub-Catchment, North-Eastern Serbia - Vranešević, Milica; Salvai, Andrea; Bezdan, Atila; Zemunac, Radoš (Journal of Environmental Geography, 2019)
The lowland area of the southeastern part of the Carpathian Basin is exposed to extreme hydrological conditions. The monitoring and analysis of the excess inland water are necessary in order to understand the scope and direction of the development of this type of flooding. When solving the problem of the drainage of an area and dimensioning drainage systems, one of the most important steps is to calculate the rate of runoff. Before calculating the rate of runoff, it is necessary to perform various analysis such as: hydrological, hydrogeological, pedological and land use analysis. The use of empirical formulas by different authors is one of the methods for determining the rate of runoff. These formulas can be of regional character, while some are applicable in different parts of the world. In this paper, the runoff coefficient and rate of runoff were calculated as indicators of the efficiency of the area drainage, employing the formulas by Nemet and Turazzo. The emphasis was put on the usage of modern tools and databases of soil characteristics while using a “traditional” method to determine rate of runoff. The obtained results demonstrate that the rate of runoff which reflects the current state of the drainage basin is very similar to the rate of runoff used for dimensioning of drainage system. The problem of retaining smaller amounts of water that remains even after the anticipated drainage deadlines can be solved with the regular maintenance of amelioration canals and additional ameliorative measures.